2021
DOI: 10.1007/s11606-021-06916-0
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Improve Diagnostic Reasoning in Undergraduate Medical Education in the Clinical Setting: a Systematic Review

Abstract: BACKGROUND: In recent years, there have been numerous studies exploring different teaching methods for improving diagnostic reasoning in undergraduate medical students. This systematic review examines and summarizes the evidence for the effectiveness of these teaching methods during clinical training. METHODS: PubMed, Embase, Scopus, and ERIC were searched. The inclusion criteria for the review consist of articles describing (1) methods to enhance diagnostic reasoning, (2) in a clinical setting (3) on medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 61 publications
0
11
0
3
Order By: Relevance
“…Timely and detailed feedback from the faculty is one of the most important strategies in developing clinical reasoning skills [ 1 , 5 , 23 , 25 , 27 ]. Feedback is regarded as effective in promoting reflective processes and enhancing learning [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Timely and detailed feedback from the faculty is one of the most important strategies in developing clinical reasoning skills [ 1 , 5 , 23 , 25 , 27 ]. Feedback is regarded as effective in promoting reflective processes and enhancing learning [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical reasoning training in the pre-clinical phase has recently been considered important. Instead of informal experiential learning with varying quality of supervision during clinical clerkships [ 5 ], the need for more structured explicit attempts to teach clinical reasoning before clinical rotations is rising. Medical schools want to address this issue by designing a clinical reasoning program for pre-clinical students [ 6 , 7 ], but it poses challenges as the best way to develop clinical reasoning is uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical reasoning has been recognized as a subject of science since the 1950s, and many medical educators are studying distinct ways to enhance clinical reasoning for medical students or junior physicians [ 12 ]. A systematic review published in 2021 reported that 12 of the 17 articles showed performance improvements among medical students after the intervention [ 13 ]. The teaching or learning styles included in these 12 articles included structured reflection, self-explanation, generating differential diagnoses, case presentation techniques, workshops with illness scripts, and schemas.…”
Section: Discussionmentioning
confidence: 99%
“…advanced practice nursing, clinical reasoning, diagnosis, diagnostic reasoning, literature review, nurse practitioner, nurse practitioner education, nursing, nursing curriculum, scoping review diagnosis (Xu et al, 2021); appropriate and relevant diagnostic testing (Steiger et al, 2011); determining the working diagnosis (Charlin et al, 2007); developing an evidence-based and patientcentred management plan (Cooper et al, 2021); reflecting on one's DR competencies (Mamede et al, 2012;Olson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%